Pengaruh Brand Ambassador dan Brand Image Terhadap Keputusan Pembelian Azarine Cosmetic - Herawati Herawati; Angga Sanita Putra (Departement of Mathematics Education, 2023)
This study aims to determine the effect of brand ambassadors and brand image on purchasing decisions of azarine cosmetics partially and simultaneously. The population in this study are people who use products from azarinecosmetic. The sample studied has a total of 50 respondents. The independent variables in this study are brand ambassadors (X1), brand image (X2) and the purchase decision dependent variable (Y). This research method uses field research by distributing questionnaires. Data analysis using SPSS linear analysis. The results of the linear regression analysis obtained the equation Y = 2.447 + 0.182 X1 + 0.361 X2. Partially, brand ambassadors can influence purchasing decisions by 18.2% and brand image can influence purchasing decisions by 36.1%. Simultaneously, brand ambassadors and brand image can influence purchasing decisions by 75.2%, the remaining 24.8% is given by other variables outside the research. The conclusion of this study is that the partial test of brand ambassadors does not have a significant influence on purchasing decisions, while brand image has a significant effect on purchasing decisions. Simultaneously, brand ambassadors and brand image have a significant influence on purchasing decisions.